KINERJA KEUANGAN SEBAGAI FAKTOR PENDUKUNG TRANSPARANSI DAN AKUNTABILITAS DALAM MEMBANGUN KEPERCAYAAN PUBLIK PADA (YKAKI) - Lutfia; Sonny Fransisco Siboro; Anggita Dhea Pramono; Putri Eka Sari Purba; Fadlan Putra P.A (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the application of the principles of transparency and accountability in the management of public funds received by this social institution. This study uses a qualitative case study approach by analyzing YKAKI's 2023 financial report, and evaluating its impact on public trust. The results of the study show that YKAKI has demonstrated a good level of transparency through the preparation of financial reports audited by independent auditors on a regular basis, as well as the provision of clear information on the use of funds and program results. In addition, the application of the principle of accountability in financial management can also be seen from reporting in accordance with accounting standards for non-profit organizations, such as ISAK No.35 / No.335.